Вплив метеоумов на хімічний склад плодів нектарина (Persica vulgaris subsp. nectarina (Ait.) Shof.) - Korniliyev, G.V.; Richter, O.O.; Ezhov, V.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The many years data about chemical composition of two nectarine varieties of different ripening periods and data during the studied years have been given. The correlation factors between the chemical composition and meteorological factors have been calculated. It is established that the meteorological factors influence very much on dry substances, disaccharides, water soluble pectin and titric acids contents.